Pengaruh Kepercayaan dan Kepuasan terhadap Loyalitas wali santri di Unit Pendidikan Formal Pondok Pesantren Riyadlul Jannah Pacet Mojokerto - Peni Indrawati (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2021)
The purpose of this study was to analyze the simultaneous, partial and dominant influence of Trust and Satisfaction on the Loyalty of the santri guardian. This type of research is explanatory research, namely research that aims to determine the relationship between the two variables Trust and Satisfaction with the Loyalty of the guardian of the santri. The research population is the guardian of the students of the Riyadlul Jannah Islamic Boarding School Formal Education Unit Pacet Mojokerto. The number of samples was 95 people, while the data analysis used multiple linear regression. The results showed that: 1) There was a simultaneous influence of trust and satisfaction on the loyalty of the guardians of students. 2) There is no partial effect of trust on the loyalty of santri guardians and there is a partial effect of satisfaction on the loyalty of santri guardians. 3) satisfaction has a more dominant effect on the loyalty of santri guardians than trust.